Tourism for whom?: Small scale bussiness women of the Goan coastline and the touristical boom - García Armand, Asun (Arenal. Revista de historia de las mujeres, 2002)
The indian state of Goa -a portuguese colony until 1961- located 594 Km south of Mumbay, on the Indian Ocean, has undergone an important touristical development from the seventies, when it became the Eldorado of the Hippy generation. This gave birth to a touristical industry, rather basic, which profited economically to the local population. Among the poorest, an important contingent of women got to start touristical and commercial activities, rapidly evolving towards a real entrepreneurial business, an "economical unit of production of goods and services" (Larousse Encyclopedia). The out-of-the-home character of these jobs as well as the benefits realised influenced the gender relations within the families, and with the immediate social surrounding. Since the end of the eighties, Goa has fallen in the hands of the promoters of a capitalist type of tourism, and in a matter of twenty years, has been converted to a sort of indian "Riviera". The following article offers an observation on the consequences that this radical change of tourism has had on the activities of these women, and confront them to the discourse of the touristical lobby, according to which the touristical development in the "Third World" countries contributes to the economical growth, the general welfare, and offers all kind of possibilities of employment of the local people. To do so, we have followed the evolution of six small female businesses between 1989 and 2002, and we have compared it with the statements of the lobby, and with our hypothesis. Those are divergent, in the sense that we observed that precisely the large scale tourism has an effect of work alienation for those persons who have little or no professional qualifications and a very limited know how; and poor investment possibilities.